Hydrogels formed by anammox extracellular polymeric substances: structural and mechanical insights - Lotti, Tommaso (Sci Rep, 2019)
The recovery of biopolymers from the waste sludge produced in wastewater treatments and their application in other industrial sectors, would substantially increase the environmental and economical sustainability of the process, promoting the development of a circular economy. In this study, extracellular polymeric substances (EPS) extracted from anammox granular waste sludge, were investigated and characterized. Rheological and differential scanning calorimetry measurements on EPS aqueous dispersions indicate the formation of an extended 3-D network above a threshold concentration, with a clear dependence of the mechanical and water retention properties on EPS content. The structural characterization, performed with transmission electron microscopy and small angle X-ray scattering, reveals the presence of functional amyloids as putative structural units, observed for the first time in an EPS-based hydrogel. As a proof of concept of the applicative potential, we explored the water and grease resistance provided to paper by an EPS coating. These results shed light on the structural details of EPS-based hydrogels, and pave the way for the possible use of EPS-based materials as a cheap, eco-friendly alternative to commonly adopted paper coatings, in line with a circular economy pattern for wastewater treatment.